Effect of HIV pre‐exposure prophylaxis (PrEP) on detection of early infection and its impact on the appropriate post‐PrEP deferral period. Issue 4 (23rd September 2020) - Seed, Clive R.; Styles, Claire E.; Hoad, Veronica C.; Yang, Hung; Thomas, Michael J.; Gosbell, Iain B.
Abstract : Introduction: HIV antivirals for pre‐exposure prophylaxis (PrEP) are known to affect detection of early HIV infection through suppression of viral load and delayed seroconversion. To cover potential delay in HIV detection associated with PrEP use by blood donors in the context of international reductions in sexual activity‐based deferral periods, we analysed the available data to determine the appropriate minimum post‐PrEP deferral period for blood donation. Materials and methods: Published cases of incident HIV infection when PrEP use was objectively demonstrable were identified, consisting principally of seroconverters from the Partners PrEP study (a clinical trial of PrEP efficacy). Data were reviewed to determine the impact of PrEP on the detection of HIV RNA, p24 Ag and seroconversion delay. Results: Nucleic acid testing (NAT) detected early HIV infection in the presence of PrEP prior to or in concordance with serological testing in approximately 90% of cases. Undetectable HIV RNA would rebound to detectable levels within two months of PrEP cessation. PrEP delayed p24 antigen detection and antibody seroconversion by about 7 days. Conclusion: Even when daily PrEP is continued, it is likely that the majority of early HIV infections are detectable by individual donation (ID)‐NAT, with p24 Ag or antibody seroconversion occurring conservatively within four weeks of exposure. HIV RNA levels also rebound rapidly in the absence of PrEP. In Australia, a three‐month deferral period for blood donation after the last dose of PrEP provides an appropriate safety margin to mitigate the residual risk of transfusion‐transmitted HIV.